The Determinant Factors of Employee Job Satisfaction - Farhan Sanjaya; Joko Suyono; Damarsari Ratnasahara Elisabeth (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The purpose of this study is to analyze the effect of human resource development, organizational culture and leadership style both simultaneously and partially on employee job satisfaction. And also to analyze the dominant influence on employee job satisfaction. Design/methodology/approach: The population in this study were 67employees of automotive muffler industry in Sidoarjo. Questionnaire was used as data collecting method and data analysis technique used was multiple linear regression. Findings: The results of data analysis prove that simultaneously and partially the development of human resources, organizational culture and leadership has a significant effect on employee job satisfaction. While the variable that has the dominant influence on employee job satisfaction is the variable of leadership style. Practical implications: The results of this research can be used as a reference to increase employee job satisfaction in manufacturing. Originality/value: The results of the research show that among the variables of human resource development, organizational culture and leadership, the leadership style has a dominant influence on customer satisfaction. This is a new phenomenon that needs to be implemented in a muffler manufacturing. Paper type: This paper can be categorized as research paper.